Access to HIV services and viral load suppression among children during the 90-90-90 strategy implementation in South Africa: A time series analysis - Juliet C.Y. Nyasulu; Innocent Maposa; Bernard P. Sikhakhane; Himani Pandya (AOSIS, 2021)
Background: During the era of the Millennium Development Goals (MDG), children were shown to have less access to human immunodeficiency virus (HIV) services than their adult counterparts; hence the call to prioritise children in the implementation of the Sustainable Development Goals (SDGs). However, South African (SA) national data in 2019 indicated that almost 3 years into the implementation of the 90-90-90 strategy, only 59% of children living with HIV had been tested for HIV compared to 90% of adults. Objectives: To evaluate the access of children to HIV services and record the viral load (VL) suppression rates during the implementation of the 90-90-90 strategy in the City of Johannesburg (COJ), South Africa. Methods: This study applied a quasi-experimental interrupted time-series (ITS) design using the monthly District Health Information System (DHIS) and National Health Laboratory Services (NHLS) databases spanning the period from 2015 to 2020, that is, before and after the implementation and roll-out of the 90-90-90 strategy. Data were extracted from these databases into MS Excel 2010 spreadsheets and analysed with Stata 15 software from Stata Corp using a two-tailed t-test at a 5% level of significance. Results: Overall, a significant increase was observed in the number of individuals tested for HIV, n = 757, p = 0.0086, and retained in care n = 2523, p = 0.001 over the whole period of analysis beginning in April 2015. Adult HIV testing, antiretroviral treatment (ART) initiation and retention in care had been decreasing in absolute numbers over a 10-month period before the intervention. An increase in these three data elements was observed following the implementation of the 90-90-90 program. On the other hand, children aged 0-15 years had demonstrated a significant increase in absolute numbers tested for HIV, n = 171, p = 0.001, but an insignificant increase in number of ART initiations, n = 14.33, p = 0.252, before implementation but a decrease after this. The overall VL suppression rates for children were lower than those of adults. Conclusion: Although the COJ has recorded progress in adult HIV testing, ART initiation and retention, children living with HIV aged 0-15 years continue to experience less access to HIV services and lower VL suppression than youths and adults of ≥ 15 years. Therefore, to ensure that the 90-90-90 targets are achieved across different age groups, children must be prioritised so that they can equally access these services with adults.